Kualitas Pelayanan Nasabah dan Dampaknya terhadap Kepuasan Nasabah pada Baitul Qiradh Amanah Nanggroe, Banda Aceh - Nurbismi Nurbismi (SI-MEN, 2019)
This study discusses the effect of user service quality on service user satisfaction on Baitul Qiradh Amanah Nanggroe, Banda Aceh. User service quality as an independent variable, has a connection to service product user satisfaction as the dependent variable. The population of respondents in this study was 1354 people, while the sample used was 93 people. Data analysis equipment used is simple linear regression. This study aims to find out how the satisfaction of user service products is influenced by the quality of services used by users or clients. This research is descriptive using quantitative methods. The results of this study indicate the quality of service influences singfikan to butterfly service users at Baitul Qiradh Amanah Naggroe in Banda Aceh.